The Rhine - Knepper, Thomas P. (Water Pollution, 2006)
The Rhine, in many ways the most important river in Europe has undergone not only tremendous contamination but also recreation. This book clearly demonstrates that the Rhine is by far the best investigated water body worldwide. Many well known scientists have presented their knowledge in this book covering a wide span of different topics. The development of the Rhine, its catchment area and hydrology is as well presented as the development of water protection requirements and early warning systems on the Rhine. Additionally the book describes many aspects of water quality from the Rhine but also from alpine lakes, tributaries, estuary and adjacent coastal waters connected with the Rhine. This work provides a great deal of data obtained from the analysis and up-to-date monitoring of organic micro pollutants, such as e.g. pesticides, pharmaceuticals, synthetic aromatic sulfonates, chelating agents, industrial chemicals and by-products from chemical syntheses.